Minahasa-Kristen Dalam Gejolak Eksistensi Antara Budaya Dan Agama - Ratuwalangon, Rocky; Sagala, Rudolf; Hutagalung, Stimson; Ferinia, Rolyana (AL-ADYAN, 2022)
This reasearch attempts to seek the possibilities and obstracles that impact Minahasan-Christian’s community in the fluctuation among culture and religion which involve in struggle and controversy in public. It leads to the unconfidence of Minahasan-Christian to express their social identity. Confirming its identity in local scope is essential and shares massive debates, moreover, in NKRI form, it faces challeges. Therefore, this essay employs qualitative approach intends to display on how culture and religion involves in intense discussion that relates to the existence of MInahasan-Christian in the state. In conclusion, the tension expresses possibilities and obstacles, the culture and religion should share common instead of involve in a battle. The Minahasan-Christian should engage deeply with religious teaching and preserve indigenous tradition and culture.